2017
DOI: 10.1126/science.aag2770
|View full text |Cite
|
Sign up to set email alerts
|

Chemical transformation of xenobiotics by the human gut microbiota

Abstract: The human gut microbiota makes key contributions to the metabolism of ingested compounds (xenobiotics), transforming hundreds of dietary components, industrial chemicals, and pharmaceuticals into metabolites with altered activities, toxicities, and lifetimes within the body. The chemistry of gut microbial xenobiotic metabolism is often distinct from that of host enzymes. Despite their important consequences for human biology, the gut microbes, genes and enzymes involved in xenobiotic metabolism are poorly unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
598
1
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 781 publications
(619 citation statements)
references
References 122 publications
(151 reference statements)
7
598
1
13
Order By: Relevance
“…The quinone reduction activities of azoreductase from different microorganisms and their dependence on NAD(P)H cofactor need to be classified as NAD(P)H quinone oxidoreductases (NQOs) (Liu et al 2008(Liu et al , 2009Ryan et al 2010a, b;Hervas et al 2012). As reviewed by Ryan (2017) and Koppel et al (2017), there are very few NQOs characterized from human gut bacterial strains. Recently, Ryan et al (2014) identified the NAD(P)H quinone oxidoreductase activity in azoreductase from P. aeruginosa and demonstrated that the azoreductases and the NAD(P)H quinone oxidoreductases belong to the same FMN-dependent azoreductase superfamily.…”
Section: Azoreductase Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The quinone reduction activities of azoreductase from different microorganisms and their dependence on NAD(P)H cofactor need to be classified as NAD(P)H quinone oxidoreductases (NQOs) (Liu et al 2008(Liu et al , 2009Ryan et al 2010a, b;Hervas et al 2012). As reviewed by Ryan (2017) and Koppel et al (2017), there are very few NQOs characterized from human gut bacterial strains. Recently, Ryan et al (2014) identified the NAD(P)H quinone oxidoreductase activity in azoreductase from P. aeruginosa and demonstrated that the azoreductases and the NAD(P)H quinone oxidoreductases belong to the same FMN-dependent azoreductase superfamily.…”
Section: Azoreductase Classificationmentioning
confidence: 99%
“…The human gastrointestinal tract contains a complex micro flora comprising at least 400-500 bacterial species. Some of them are isolated and characterized with high activity of azo nitroreductase in the presence of flavins and NAD(P)H (Rafii and Cerniglia 1995;Koppel et al 2017). However, the precise role of azoreductases in drug metabolism is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…Our bacterial population contains millions of genes 2 encoding enzymes that can process substances that have been derived from nutrients or the environment, or that have been administered as drugs. Such metabolism generates other compounds that can affect host homeostasis 3 . However, microbial metabolism is not always beneficial for the host.…”
Section: H R I St I a N J O B I Nmentioning
confidence: 99%
“…This is particularly true for experiments at the Large Hadron Collider near Geneva, Switzerland, where particle collisions occur up to 40 million times per second 1 , generating enormous data sets. These data sets often involve only a tiny number of the particles of interest -for instance, the particles called Higgs bosons are produced approximately once every billion collisions 2,3 . On page 375, Mott et al 4 report a data-analysis technique that unites machine learning and quantum computing, and apply it to the problem of identifying Higgs bosons.…”
Section: St E V E N S C H R a M Mmentioning
confidence: 99%